The Labor Market Effects of Payroll Taxes in a Middle-Income Country: Evidence from Colombia - Adriana D. Kugler; Maurice Kugler (Institute for the Study of Labor (IZA), 2003)
We use a panel of manufacturing plants from Colombia to analyze how the rise in payroll tax rates over the 1980?s and 1990?s affected the labor market. Our estimates indicate that formal wages fall by between 1.4% and 2.3% as a result of a 10% rise in payroll taxes. This ?less-than-full-shifting? is likely to be the result of weak linkages between benefits and taxes and the presence of downward wage rigidities induced by a binding minimum wage in Colombia. Because the costs of taxation are only partly shifted from employers to employees, employment should also fall. Our results indicate that a 10% increase in payroll taxes lowered formal employment by between 4% and 5%. In addition, we find less shifting and larger disemployment effects for production than non-production workers. These results suggest that policies aimed at boosting the relative demand of low-skill workers by reducing social security taxes on those with low earnings may be effective in a country like Colombia, especially if tax cuts are targeted to indirect benefits.
Keywords: J31; H23; J32; 330; payroll taxes; shifting; wage rigidity; minimum wages; Lohnsummensteuer; Steuerwirkung; Beschäftigungseffekt; Lohnrigidität; Mindestlohn; Schätzung; Kolumbien